Spiritually Based Interventions for High Blood Pressure: A Systematic Review and Meta-analysis - Khabiri, Roghayeh (Journal of religion and health, 2024)
This systematic review and meta-analysis aimed to evaluate the effectiveness of spiritually based interventions on blood pressure (BP) among adults. A systematic search was performed using the PubMed, Scopus, and Cochrane databases to identify studies evaluating spiritual interventions, including meditation, transcendental meditation, mindfulness meditation, and yoga, for high BP among adults up to January 1, 2022. The inclusion criteria were (a) randomized controlled trials (RCTs), (b) studies in English or Persian, (c) studies conducted among adults (≥ 18 years), and (d) studies reporting systolic or diastolic BP. Given the high heterogeneity of these studies, a random effect model was used to calculate the effect sizes for the RCTs. In total, the systematic review included 24 studies and the meta-analysis included 23 studies. As some of studies reported two or more outcome measurements, separate estimates of each outcome were extracted for that study (24 datasets). Fifteen trials reported the mean (SD) systolic blood pressure (SBP), and 13 trials reported the mean (SD) diastolic blood pressure (DBP). In addition, 13 studies reported means (SDs) and six trials reported mean changes in DBP. A significant decrease was found in systolic BP following intervention ((WMD (weighted mean difference) =  − 7.63 [− 9.61 to − 5.65; P < 0.001]). We observed significant heterogeneity among the studies (I2 = 96.9; P < 0.001). A significant decrease was observed in DBP following the interventions (WMD =  − 4.75 [− 6.45 to − 3.05; P < 0.001]). Spiritually based interventions including meditation and yoga had beneficial effects in reducing both SBP and DBP. Reducing BP can be expected to reduce the risk of cardiovascular diseases.